Measuring health and economic wellbeing in the Sustainable Development Goals era: development of a poverty-free life expectancy metric and estimates for 90 countries - Carlos Riumallo-Herl, PhD; David Canning, ProfPhD; Joshua A Salomon, ProfPhD (Elsevier, 2018)
Summary: Background: The Sustainable Development Goals (SDGs), adopted in September, 2015, emphasise the link between health and economic development policies. Despite this link, and the multitude of targets and indicators in the SDGs and other initiatives, few monitoring tools explicitly incorporate measures of both health and economic status. Here we propose poverty-free life expectancy (PFLE) as a new metric that uses widely available data to provide a composite measure of population health and economic wellbeing. Methods: We developed a population-level measure of PFLE and computed this summary measure for 90 countries with available data. Specifically, we used Sullivan's method, as in many health expectancy measures, to incorporate the prevalence of poverty by age and sex from household economic surveys into demographic life tables based on mortality rates from the 2015 Global Burden of Disease Study (GBD). For comparison, we also recalculated all PFLE measures using life tables from WHO and the UN. PFLE estimates for each country, stratified by sex, are the average number of poverty-free years a person could expect to live if exposed to current mortality rates and poverty prevalence in that country. Findings: The average PFLE in the 90 countries included in this study was 66·0 years (95% uncertainty interval [UI] 64·5-67·3) for females and 61·6 years (60·1-62·9) for males, whereas life expectancy estimates were 76·3 years (95% UI 74·0-78·2) for females and 71·0 years (68·7-73·0) for males. PFLE varied widely between countries, ranging from 9·9 years (95% UI 9·1-10·5) for both sexes combined in Malawi, to 83·2 years (83·0-83·5) in Iceland, the latter differing only marginally from life expectancy in that country. In 67 of 90 countries, the difference between life expectancy and PFLE was greater for females than for males, indicating that women generally live more years of life in poverty than men do. Results were consistent when using GBD, WHO, or UN life tables. Interpretation: Differences in PFLE between countries are substantially greater than differences in life expectancy. Despite general improvements in survival in most regions of the world in the past decades, the focus in the SDG era on ending poverty brings into sharp relief the importance of ensuring that years of added life are lived with at least a minimum standard of economic wellbeing. Although summary measures of population health provide overall measures of survivorship and functional health, our new measure of PFLE provides complementary information that can inform and benchmark policies seeking to improve both health and economic wellbeing. Funding: None.